Pemberdayaan Masyarakat dalam Inovasi Bahan Pangan dari Limbah Biji Mangga di SMKN 1 Pemulutan, Sumatera Selatan - Nurisman, Enggal; Agustina, Tuty Emilia; Melwita, Elda; Jannah, Asyeni Miftahul; Pritania, Alya Dewi (Universitas Nusantara PGRI Kediri, 2024)
Mango seeds (Mangifera indica L.) have a fairly high carbohydrate content and can be processed as an alternative food. This community service activity aims to educate the public about the process of processing mango seeds into flour and processed food ingredients. Prior to counseling, the team conducted initial experiments on the products produced using initial treatment in the form of soaking with water, slaked lime and sodium bisulfite. Organoleptic tests on processed food products from mango seeds were carried out by random respondents with assessment indicators in the form of color, texture, aroma and taste. The test results showed that processed cakes from mango seed flour as much as 30% with the initial treatment of sodium bisulfite immersion in the initial process had the best organoleptic value, namely, 3.7 out of 4. This activity was carried out at SMKN 1 Pemulutan and received very good appreciation because it was considered very useful, informative and can be developed continuously.